1994
DOI: 10.1073/pnas.91.24.11323
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of calcium-binding sites in the kidney stone inhibitor glycoprotein nephrocalcin with vanadyl ions: electron paramagnetic resonance and electron nuclear double resonance spectroscopy.

Abstract: This inhibitor protein has been isolated in four isoforms from urine of normal subjects (1) and kidney stone patients (2), from surgically removed calcium oxalate kidney stones (3), and from kidney tissue of nine species of vertebrates (4). Among these nine species, the dissociation constant of these inhibitor proteins for binding COM crystals varies from 6 x 10-6 to 4 x 10-8 M. Purification of NC from bovine kidney tissue by DEAE-cellulose chromatography showed that it also consists offour isoforms, which hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…Only in aqueous solution is the fourth species D observed. Its spectrum yields g-and A-values identical to those of the [VO(H 2 O) 5 ] 2ϩ ion (9,26,28). However, no previous study has shown the equivalence of species A, B, and C in aqueous solution to AЈ, BЈ, and CЈ, respectively, in methanol.…”
Section: The Ph Dependence Of the Epr Spectrum Of Vo(acac) 2 -Figmentioning
confidence: 78%
See 1 more Smart Citation
“…Only in aqueous solution is the fourth species D observed. Its spectrum yields g-and A-values identical to those of the [VO(H 2 O) 5 ] 2ϩ ion (9,26,28). However, no previous study has shown the equivalence of species A, B, and C in aqueous solution to AЈ, BЈ, and CЈ, respectively, in methanol.…”
Section: The Ph Dependence Of the Epr Spectrum Of Vo(acac) 2 -Figmentioning
confidence: 78%
“…EPR and ENDOR spectra were recorded with an X-band Bruker ESP 300E spectrometer equipped with a cylindrical TE 011 ENDOR cavity, an Oxford Instruments ESR910 liquid helium cryostat, and Bruker ENDOR digital accessory as described previously (25,26). The ESP 300E spectrometer was equipped with a complete computer interface (Bruker ESP3220 data system) for spectrometer control and data acquisition and processing.…”
Section: Methodsmentioning
confidence: 99%
“…However, the identification of additional substrates with diverse functions such as the bone proteins osteocalcin and MGP, the kidney proteins nephrocalcin A-D, and the signaling molecule GAS6, [13][14][15][16] together with the expression of ␥-carboxylase in multiple tissues, 3 all suggest a broader function for this posttranslational modification, in addition to its role in forming the membrane-binding domains of the vitamin K-dependent blood coagulation and regulatory proteins. 37 Further support for this notion comes from the identification of the conservation of the ␥-carboxylase gene in Ciona intestinalis and other chordates, 5 as well as in Drosophila and Conus snail species, 6,7 organisms which arose well before the evolution of the known vitamin K-dependent coagulation factors.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, knockout mice with complete deficiency of prothrombinase or prothrombin exhibit an embryonic lethal phenotype in approximately one-half of animals, possibly due to loss of a required early developmental signal through the thrombin receptor, with the remaining mice dying at term of massive hemorrhage. [9][10][11][12] Other mammalian proteins known to undergo ␥-carboxylation include osteocalcin, matrix Gla protein (MGP), 13 Gas6, 14 nephrocalcin A-D, 15 the proline-rich ␥-carboxylated proteins (PRGP-1 and PRGP-2), 16 and the transmembrane proteins TMG3 and TMG4. 17 ␥-Carboxylation is absolutely required for function of the vitamin K-dependent blood coagulation factors.…”
Section: Introductionmentioning
confidence: 99%
“…Nephrocalcin (NC) also inhibits CaOx nucleation and aggregation, and crystal adhesion to renal cells [6,9]. One mole of NC binds 4 mol of Ca 2+ , and its binding sites differ completely from those in other Ca 2+ -binding proteins [10]. NC is produced in the human kidney by the proximal tubule and the thick ascending limb of Henle's loop.…”
Section: Nephrocalcinmentioning
confidence: 99%